Current Limitations of the Assessment of Haemostasis in Adult Extracorporeal Membrane Oxygenation Patients and the Role of Point-of-Care Testing. Issue 6 (November 2016) - Venkatesh, K.; Nair, P. S.; Hoechter, D. J.; Buscher, H.
Haemostatic perturbations are commonly seen in extracorporeal membrane oxygenation (ECMO) patients and remain a clinical challenge, contributing significantly to morbidity and mortality. The approach to anticoagulation monitoring and the management of bleeding varies considerably across ECMO centres. Routine laboratory tests have their limitations in terms of turnaround time and specificity of information provided. Newer point-of-care testing (POCT) for coagulation may overcome these issues, as it provides information about the entire coagulation pathway from clot initiation to lysis. It is also possible to obtain qualitative information on platelet function from these tests. Furthermore, the ability to incorporate these results into a goal-directed algorithm to manage bleeding with targeted transfusion strategies appears particularly attractive and cost effective. Further studies are required to evaluate the utility of POCT to optimise bleeding and anticoagulation management in these complex patients.